НОВЫЙ БИОЛОГИЧЕСКИЙ ПРЕПАРАТ ДЛЯ ЗАЩИТЫ СЕЛЬСКОХОЗЯЙСТВЕННЫХ РАСТЕНИЙ ОТ ФИТОПАТОГЕННЫХ ГРИБОВ (Experimental biology, 2015)
The basis of the production of new, effective and economical kazakchstan`s biopreparation "Bacirin" for protection agricultural plants against phytopathogenic fungi causing root rot of the cereals was developed. Thisbiopreparation stimulates growth agricultural plants.
Keywords: biopreparation "Bacirin"